Peran Edukasi Keuangan Syariah dalam Membentuk Perilaku Keuangan dan Implikasinya terhadap Inklusi Perbankan Syariah - Maula Nasrifah (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2025)
The development of Islamic banking in Indonesia has shown significant growth in terms of institutional expansion and regulatory support; however, its level of inclusion remains relatively lower than that of conventional banking. One of the key factors contributing to this condition is the limited level of Islamic financial literacy among the public. This study aims to analyze the role of Islamic financial education in shaping financial behavior and its implications for enhancing Islamic banking inclusion in Indonesia. This research employs a descriptive qualitative approach using document-based analysis of policy reports, regulations, and relevant national and international academic literature. Data were analyzed through thematic qualitative analysis to identify the relationships between Islamic financial education, financial literacy, financial behavior, and Islamic banking inclusion. The findings indicate that Islamic financial education plays a fundamental role in improving Islamic financial literacy and fostering financial behavior aligned with Sharia principles. Such behavioral changes contribute to increased public participation in utilizing Islamic banking services. This study emphasizes that the enhancement of Islamic banking inclusion should be understood as a continuous socio-educational process rather than merely an issue of financial access.